Confessions of a scholarship winner : the secrets that helped me win $500,000 in free money for college : how you can too! - Ellis, Kristina (Worthy Publishing, 2013)
On the first day of high school, Kristina Ellis's mom, a single, working mother who lost her husband to cancer, informed her that she could not financially support her after graduation. Kristina would need to find her own way to pay for college. As an average student with less-than-impressive test scores, Kristina realized she would have to sell herself to scholarship committees if she wanted to stand out. That's when she devised the plan that led to her receiving over $500,000 in free money for college--enough to pay for her full education at a top-20 university, all the way up to her doctoral degree, and make her dreams come true. How she made it happen--and how you can too!--is the focus of this book. Kristina shares not just her little-known secrets for scholarship success but her incredibly inspiring story --